2006
DOI: 10.1248/bpb.29.1441
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Calvert's Formula for Dosage Adjustment of Carboplatin in Japanese Patients with Hormone Refractory Prostate Cancer

Abstract: Carboplatin, an analogue of cisplatin, was introduced in 1981 and has proven effective against various malignancies. Carboplatin has less nonhematological toxicity such as renal failure than its parent compound cisplatin, 1) and thrombocytopenia is a dose-limiting factor of this drug.2) Since the 1990's, carboplatin in combination with paclitaxel has been used in the treatment of several solid tumors such as ovarian, breast and lung cancers. [3][4][5] At present, no chemotherapy is considered effective enough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This analytical procedure was validated in terms of selectivity specifi city, recovery, linearity, LLOQ, precision and accuracy. Our procedure eliminates the need for solid-phase extraction, nitrogen evaporation, ICP and MS (Sato et al, 2006;Falter and Wilken, 1999). Mass spectrometry and ICP are very expensive, require extensive training and are not readily available in veterinary hospitals for drug analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This analytical procedure was validated in terms of selectivity specifi city, recovery, linearity, LLOQ, precision and accuracy. Our procedure eliminates the need for solid-phase extraction, nitrogen evaporation, ICP and MS (Sato et al, 2006;Falter and Wilken, 1999). Mass spectrometry and ICP are very expensive, require extensive training and are not readily available in veterinary hospitals for drug analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search revealed that there are several methods for quantifi cation of carboplatin in human plasma (Doz et al, 1998;Burns and Embree, 2000;Zufi a et al, 2001;Leger et al, 2002;Sato et al, 2006). Some of the methods involve post column derivatization, solid-phase extraction (Burns and Embree, 2000), ultrafi ltration and evaporation , the use of ICP-MS with nebulisation (Falter and Wilken 1999;Sato et al, 2006), LC-MS (Guo et al, 2003) and atomic absorption (Leger et al, 2002;Doz et al, 1998). However, appropriate methods for quantifi cation of carboplatin in dog plasma are scarce and high-tech instruments like LC-MS and ICP-MS are costly and not widely available in veterinary hospitals for drug quantitation.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, bone marrow suppression of carboplatin is not related to the administered dose but the area under the curve (AUC) of plasma concentration versus time of exposed . Similar relationships have been also studied between carboplatin AUC and antitumor effect . As carboplatin is mainly eliminated by the kidneys, the dose of carboplatin for a patient usually depends on his or her renal function .…”
Section: Introductionmentioning
confidence: 99%
“…As carboplatin is mainly eliminated by the kidneys, the dose of carboplatin for a patient usually depends on his or her renal function . To obtain therapeutic benefits or reduce adverse effect, therapeutic drug monitoring of carboplatin could be an effective tool to adjust dose of carboplatin for people with impaired renal function even those who receive hemodialysis . Therefore, determining the plasma target concentration of carboplatin and elucidating the variation in pharmacokinetics is required .…”
Section: Introductionmentioning
confidence: 99%